Managing Project Boundaries: Best Practices, Challenges, and Tools for Successful Implementation - Bambang Ermansyah Saragih; Dewi Listiorini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Managing project boundaries is critical to ensuring that projects are completed on time, within budget, and according to stakeholder expectations. This research investigates key methodologies and tools for managing project boundaries, with a focus on best practices, challenges, and technology. Case studies, qualitative interviews, and quantitative analysis explore the consequences of mismanagement, such as scope creep and resource misallocation. Findings suggest that clear documentation, stakeholder alignment, and modern project management tools reduce these risks and lead to successful project outcomes. Practical recommendations for improving boundary management practices are provided